Apoyo familiar y su influencia en las conductas desadaptativas de un niño - Moreno Avilez, Santiago (2021)
This research work refers to the analysis and psychological intervention of a child with maladaptive behavior and the support they receive from the family environment in its development, the objective of the case was established, which consists of “establishing how the family support in the maladaptive behaviors of a child and propose a therapeutic plan that allows improving family interaction ”and from the theoretical conception it is possible to show that the support of parents in the development of inappropriate behavior in childhood is essential, although it is also there are other risk factors, such as socioeconomic level, domestic violence, age of the child. To address this issue, a child-age patient has been considered, to which two psychometric tests and several clinical interviews were applied, reaching the conclusion that the child presents maladaptive behavior due to the multiple situations presented during his cut. lifetime.